The Dismissal of Mykhailo Drahomanov from the University of St. Volodymyr: Text, Subtext, Context - Pikhmanets, Roman (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses the motives and circumstances surrounding the dismissal of Mykhailo Drahomanov from Kyiv University. There is an emphasis on the interdependence of this episode and the Ems Ukaz, its connection with Drahomanov’s Ukrainophile campaign, his previous plans and intentions regarding an overseas publication. The author provides clarifications and corrections of the commonly held perceptions of the above-mentioned events